Exploring the Impact of Financial Development on Ecological Footprint: Insights from a Decade of Bibliometric Evidence - Tlili, Haykel (International Journal of Energy Economics and Policy, 2025)
This study explores the complex relationship between financial development and ecological footprint, a subject of increasing global importance at the intersection of finance, sustainability, and environmental management. Using the Dimensions database and the bibliometric tool VOSviewer, we analyzed 124 documents published between 2015 and 2024. The analysis identifies key trends, leading contributors, thematic clusters, and collaborative networks, shedding light on how financial systems impact ecological outcomes. Our findings emphasize the growing significance of sustainable finance, including instruments like green bonds and ESG-compliant investments, in addressing the environmental challenges linked to financial development. Regional insights show that China, Pakistan, and Turkey lead research efforts in this field, while growing contributions from Africa and the Middle East underscore the global reach of this topic. Revisiting the Environmental Kuznets Curve hypothesis, the study demonstrates that strong governance and financial innovation are key to accelerating transitions toward sustainable economies. This research makes valuable contributions by offering actionable insights for policymakers, practitioners, and scholars. It underscores the need for tailored financial strategies, interdisciplinary collaboration, and technological advancements to address ecological challenges effectively. By providing a replicable framework, this study lays the groundwork for future research and practical solutions to balance economic growth with environmental conservation.